Passive cooling of Li-Ion cells with direct-metal-laser-sintered aluminium heat exchangers filled with phase change materials. (5th June 2020) - Landini, S.; Waser, R.; Stamatiou, A.; Ravotti, R.; Worlitschek, J.; O'Donovan, T.S.
Highlights: Novel Direct-Metal-Laser-Sintered (DMLS) Aluminium Heat Exchangers (HEX). DMLS HEX filled with Phase Change Materials (PCM) for Li-Ion cells isothermalisation. Different operating conditions tested by changing cell cycles and boundary conditions. Cells isothermalisation improved by PCM DMLS HEX compared to natural convection. Abstract: Operating Li-Ion cells at adverse temperatures can lead to performance decrease and faster ageing effect. A thermal management system (TMS) designed to guarantee the cells isothermal condition is therefore necessary. Phase Change Materials (PCM) can form part of an efficient TMS based on passive cooling. However, when Li-Ion cells are exposed to extreme electrical regimes, PCMs cannot recover all of the latent heat due to their low thermal conductivity. This study experimentally investigates the isothermal performance of PCMs integrated with Direct-Metal-Laser-Sintered (DMLS) aluminium heat exchangers (HEX) as a passive TMS. The DMLS HEXs are employed to enhance the equivalent thermal conductivity of the TMS and thermally connect the Li-Ion cell to the PCM. The TMS performance is evaluated in terms of cell average surface temperature and temperature uniformity. Single and consecutive cycles at different discharge rates are imposed to simulate intermittent and constant loads. To assess the TMS sensitivity to the thermal boundary conditions, the HEX is either insulated or surrounded by the ambient air. Under single discharge cycles, the cell temperature rise and temperature disuniformity decrease using the PCM HEX in both thermal boundary conditions compared to relying on air natural convection. Under consecutive cycles, the temperature rise is minimised when the PCM HEX is not insulated. These results show that PCMs show great potential as a passive TMS for a variety of Li-Ion cells' operating conditions. However, the optimisation of the PCM-TMS design is found to be case-dependent.